Can the Chinese bond market facilitate a globalizing renminbi? - Guonan Ma; Wang Yao (Bank of Finland, Institute for Economies in Transition (BOFIT), 2016)
A global renminbi needs to be backed by a large, deep and liquid renminbi bond market with a world-class Chinese government bond (CGB) market as its core. China's CGB market is the seventh largest in the world while sitting alongside a huge but non-tradable and captive central bank liability in the form of required reserves. By transforming the non-tradable cen-tral bank liabilities into homogeneous and tradable CGBs through halving the high Chinese reserve requirements, the size of the CGB market can easily double. This would help over-come some market impediments and elevate the CGBs to a top three government bond mar-ket globally, boosting market liquidity while trimming distortions to the banking system. With a foreign ownership similar to that of the JGBs, CGBs held by foreign investors may increase ten-fold by 2020, approaching 5 percent of the 2014 global foreign reserves and facilitating a potential global renminbi, especially in the wake of the renminbi's inclusion into the basket of the IMF Special Drawing Rights.
URN:NBN:fi:bof-201602161028
Keywords: F02; E42; E44; E58; G10; H63; 330